2007
DOI: 10.1086/518140
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immunity and Antibody Responses Elicited by Attenuated Salmonella enterica Serovar Typhi Strains Used as Live Oral Vaccines in Humans

Abstract: The development of improved typhoid vaccines is a high global public health priority. However, their development has been hampered by a lack of information regarding the specific determinants of protective immunity to Salmonella enterica serovar Typhi (S. Typhi) infection in humans. Although antibodies to S. Typhi O, H, and Vi appear to be involved in protection against S. Typhi infection, it is unknown whether such antibodies mediate protection, act in conjunction with other adaptive responses, or serve as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 28 publications
13
103
0
Order By: Relevance
“…Cell-mediated immune responses, in addition to antibody responses and innate immunity, are clearly involved in the response to S. Typhi infection, but it is still unclear if all are required to clear the infection, if there is a temporal requirement for each, and whether the type of response is dependent on the individual (27,40,44,47,50). Additionally, we have noted the significance of nonantibody, serum-opsonizing factors in the serum, which also need identification and characterization.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cell-mediated immune responses, in addition to antibody responses and innate immunity, are clearly involved in the response to S. Typhi infection, but it is still unclear if all are required to clear the infection, if there is a temporal requirement for each, and whether the type of response is dependent on the individual (27,40,44,47,50). Additionally, we have noted the significance of nonantibody, serum-opsonizing factors in the serum, which also need identification and characterization.…”
Section: Discussionmentioning
confidence: 96%
“…Work performed by several groups over the past decade has clarified the role of cell-mediated immune responses to S. Typhi, particularly the role of CD8 ϩ T cells (15,30,40). The role of the humoral immune response is not as well defined.…”
mentioning
confidence: 99%
“…Consequently, pathways involved in antigen processing and presentation by antigen-presenting cells, including dendritic cells, and the ability to effectively initiate antigen-specific B-and T-cell responses within the Peyer's patches, may be uniquely stimulated in animals infected with dam mutant Salmonella (54,55). Such immune responses may facilitate cross-protection due to the stimulation of the following: (i) cross-reactive opsonizing antibodies that enhance bactericidal activities of macrophages and dendritic cells by targeting infecting bacteria for efficient lysosomal degradation (29,58,60); (ii) cross-reactive blocking antibodies capable of inhibiting the infection of nonphagocytic cells which are inherently deficient in bactericidal activities; and (iii) memory CD4 ϩ and CD8 ϩ cells that confer cell-mediated activities that facilitate immune defenses or are directly cytotoxic to infected cells (45,56). While it has been reported that both antigen-specific IgG antibodies and memory T cells are required for protection against disease following challenge with homologous Salmonella (39-42, 45, 46), these data suggest that the efficiency of cross-protective immunity following dam mutant immunization may have a similar set of requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Interspersed along the length of the human intestine, the largest immunologic organ of the body, is a myriad of lymphoid tissue aggregates overlain with microfold (M) cells, specialized epithelial cells that serve as antigen-sampling ports and inductive sites for immune responses (58). Depending on the route of immunization (mucosal versus parenteral) and the nature of the vaccine, various elicited effector immune responses can contribute to protection against infection with an enteric pathogen (59)(60)(61). If the titers of antigen-specific serum IgG following administration of a parenteral vaccine are sufficiently high, antibodies that transude onto the mucosal surface can interfere with invasive and noninvasive enteric pathogens (60).…”
Section: Host Susceptibilitymentioning
confidence: 99%